Rancang Bangun Miniatur Pembagkit Listrik Tenaga Air Untuk Rumah Tangga - Syarif Ishak Allkadri (entries, 2023)
Miniature hydropower is a small system or small-scale model of a hydroelectric power plant (PLTA) designed to produce electrical energy from hydropower using principles and components similar to those of a full-scale hydropower plant. Miniature hydropower is designed as a representation or simulation of the actual hydropower, but in a smaller size and lower power capacity. The working principle of a miniature Hydroelectric Power Plant (PLTA) is based on the conversion of the kinetic energy of water into mechanical energy and then into electrical energy. This miniature hydropower plant generates DC current electric energy with water pressure from the help of a Fish Pom machine and a Tape dynamo to rotate the wheel so that the rotation can be transmitted to the generator/dynamo to be used as electricity. This miniature hydropower occurs if when the Pom Fish engine is energized from a source it will put pressure on the water so that the wheel can rotate also assisted by a Tape dynamo which is sourced from a battery charge lamp so that the rotation can move a little fast. The existing load affects the speed of the Blender generator/dynamo because the power generated is limited, therefore with the help of the Drill Cas Battery it will have an impact on the resulting rotation, so that the power generated is maximized towards the load. Keywords: Miniature Hydropower, Pom Fish Machine, Dynamo Tape, Battery Cas Lamp, Waterwheel, Dinamo Blender, Drill Battery Cas, and DC Current.